Pubic Hair Preferences, Reasons for Removal, and Associated Genital Symptoms: Comparisons Between Men and Women. (1st January 2015) - Butler, Scott M.; Smith, Nicole K.; Collazo, Erika; Caltabiano, Lucia; Herbenick, Debby
ABSTRACT: Introduction: Pubic hair grooming and removal are common behaviors among men and women. However, little is known about the reasons for grooming, preferred pubic hairstyle of sexual partners, and symptoms associated with regular grooming. Aims: This study aims to assess pubic hair removal/grooming practices, pubic hairstyle preferences, and genital outcomes associated with pubic hair removal among men and women in a college sample. Methods: Data were gathered from 1, 110 participants (671 women and 439 men) at a large public Midwestern university and a small Southern public university. Main Outcome Measures: Items assessed demographics, pubic hair grooming and removal practices in the past 4 weeks, reasons for pubic hair status, preference for pubic hairstyle of sexual partners, and symptoms associated with removal and grooming. Results: Most (95%) participants had removed their pubic hair on at least one occasion in the past 4 weeks with shaving being the most commonly reported hair removal technique by women (82%) and men (49%). Women were significantly more likely to report their typical status as hair-free (50% vs. 19%; χ 2 = 165.528, P < 0.001) and men were significantly more likely to prefer a hair-free sexual partner (60% vs. 24%; χ 2 = 211.712, P < 0.001). Genital itching was experienced on at least one occasion by 80.3% of pubic hair groomers and was the most commonly reported side effect. Conclusion: Genital grooming and pubic hair removal are common practices among both men and women of college-age. Women are likely to report stronger associations with feelings of cleanliness, comfort, sex appeal, social norms of their peer group, and affordability as reasons for their chosen pubic hair style. Women also report more experiences with genital side effects of pubic hair removal, an expected result as women are removing pubic hair more frequently and more completely than their male counterparts.